An Analytical Model for Concentration of Water Pollutant (International Journal of Scientific Research and Management (IJSRM), 2021)
In this paper, an advection- dispersion equation for the pollutant concentration is solved assuming zero initial rate of pollutant. To solve the dispersion equation in unsteady state condition, the transformation technique has been used. .It is obtained that the concentration of the pollutants in a small river decreases continuously with increasing distance.